2004
DOI: 10.1523/jneurosci.1659-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Excitability of Ascending and Descending Inputs to Cerebellar Climbing Fibers during Locomotion

Abstract: The inferior olive climbing fiber projection plays a central role in all major theories of cerebellar function. Therefore, mechanisms that control the ability of climbing fibers to forward information to the cerebellum are of considerable interest. We examined changes in transmission in cerebro-olivocerebellar pathways (COCPs) and spino-olivocerebellar pathways (SOCPs) during locomotion in awake cats (n ϭ 4) using low-intensity electrical stimuli delivered to the contralateral cerebral peduncle or the ipsilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…As has been established previously, a number of criteria allow climbing fiber-evoked potentials to be distinguished from those generated by mossy fiber activity, in particular, the following: (1) the onset latency of climbing fiber field potentials (CFPs) are always Ͼ9 ms and therefore longer than those dependent on most direct pathways terminating as mossy fibers (Ekerot and Larson, 1973); and (2) CFPs are depressed after a second stimulus delivered 40 ms after the first, whereas mossy fiber field potentials (MFPs) are usually unchanged or facilitated ( Fig. 1 A, B) (Armstrong and Harvey, 1968;Apps and Lee, 1999;Pardoe et al, 2004). As verification, we recorded single-unit Purkinje cells (in both awake and anesthetized animals) in which the evoked complex spike activity mirrored components of the field potential ascribed to climbing fiber activity at the same location (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As has been established previously, a number of criteria allow climbing fiber-evoked potentials to be distinguished from those generated by mossy fiber activity, in particular, the following: (1) the onset latency of climbing fiber field potentials (CFPs) are always Ͼ9 ms and therefore longer than those dependent on most direct pathways terminating as mossy fibers (Ekerot and Larson, 1973); and (2) CFPs are depressed after a second stimulus delivered 40 ms after the first, whereas mossy fiber field potentials (MFPs) are usually unchanged or facilitated ( Fig. 1 A, B) (Armstrong and Harvey, 1968;Apps and Lee, 1999;Pardoe et al, 2004). As verification, we recorded single-unit Purkinje cells (in both awake and anesthetized animals) in which the evoked complex spike activity mirrored components of the field potential ascribed to climbing fiber activity at the same location (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, studies in which mapping of cerebellar cortical zones in the barbiturate-or propofolanesthetized cat have been used to guide the insertion of recording microwires into the cerebellar cortex have found that the climbing fiber responses obtained from individual microwires in the awake animal displayed the same pattern of peripheral input as the zone in which they were implanted (Pardoe et al, 2004). Together, these findings suggest that the cerebellar cortical territory in which particular climbing fiber responses occur is not constrained by the choice of anesthetic and that the degree of segregation of climbing fiber inputs is maintained in the awake animal.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…For example, it seems remarkable that climbing fiber responses in vermal lobule VII may be triggered from the prelimbic cortex (Watson et al, 2009) which does not qualify as a major disynaptic source to this region. Of course, although to some extent the cerebro-olivo-cerebellar pathway is disynaptic (Lee and Kim, 2012), it usually involves more synapses (Baker et al, 2001;Pardoe et al, 2004).…”
Section: Role Of Extra-pontine Routesmentioning
confidence: 99%